Improved Design of Ultrasonic Cleaning Tank Using Harmonic Response Analysis in ANSYS - W Tangsopa; T Keawklan; K Kesngam; S Ngaochai; J Thongsri (My University, 2018)
Ultrasonic cleaning tank is a machine that many factories widely used to clean objects. At one factory, a problem occurred in the cleaning process, resulting in the factory not being able to clean objects, but cracks also appeared on some objects. It was anticipated that these were caused by uneven acoustics pressure distribution which resulted in unsuitable cavitation. This directly affected cleaning performance within the tank. In order to improve the tank's efficacy, in this research, we used Harmonic Response Analysis in ANSYS 17.2 to simulate the occurrence of acoustic pressure in the tank to find a suitable type and placing position of the transducer for the tank. We found that transducers made from PZT4 gives greater acoustic pressure than those made from PZT8. Changing the transducer type does not affect the acoustic pressure pattern. PZT4 is therefore the most suitable type of transducer for this tank. Simulation results also suggested that placing the transducer under and beside the tank will result in intense acoustic pressure that is evenly dispersed throughout the tank. Results from this simulation were then passed to the manufacturing factory, and were later accepted that it could truly enhance the tank's efficacy. Information regarding the issue was also used in the development of improved design of ultrasonic cleaning tank to have greater performance levels.
Keywords: Factory (object-oriented programming); Harmonic; Ultrasound and Cavitation Phenomena